Low levels of natural IgM antibodies against phosphorylcholine are independently associated with vascular remodeling in patients with coronary artery disease - Gleißner, Christian A.; Erbel, Christian; Häussler, Julia; Akhavanpoor, Mohammadreza; Domschke, Gabriele; Linden, Fabian; Dösch, Andreas; Buß, Sebastian Johannes; Hofmann, Nina; Gitsioudis, Gitsios; Katus, Hugo; Korosoglou, Grigorios (Clinical research in cardiology, 2015)
Low anti-phosphorylcholine (PC) IgM plasma levels have been associated with increased incidence of adverse events in coronary artery disease (CAD). The underlying mechanisms are unclear. We hypothesized that atheroprotection mediated by anti-PC IgM antibodies is associated with reduced vascular remodeling and therefore tested whether anti-PC IgM plasma levels independently predict vascular remodeling. In a prospective cross-sectional study, anti-PC IgM plasma levels were measured in 175 consecutive patients with suspected CAD undergoing cardiac computed tomography angiography. Plaque morphology was thoroughly analyzed. Vascular remodeling was defined by a change in the vessel diameter at the plaque site in comparison to the reference segment proximal to the lesion (reference diameter) of ≥10 %. Mean age of the patients was 64.8 ± 10.7 years, 48.6 % were female. In 98 patients CAD was diagnosed, 57 (58.2 %) of which displayed non-obstructive CAD (stenosis <50 %), whereas 41 (41.8 %) exhibited obstructive CAD (stenosis ≥50 %). In 34 of 98 (34.7 %) CAD patients vascular remodeling was present. Mean anti-PC IgM levels did not differ between patients with and without CAD (70.8 ± 52.7 vs. 69.1 ± 55.1 U/mL). However, anti-PC IgM levels were significantly lower in CAD patients compared to those without vascular remodeling (46.6 ± 31.6 vs. 73.3 ± 58.5 U/mL, P = 0.024). Using multivariate logistic regression, anti-PC IgM plasma levels independently predicted coronary vascular remodeling (HR 0.322, 95 % confidence interval 0.121-0.856, P = 0.023). In conclusion, low anti-PC IgM levels are independently associated with coronary vascular remodeling. These findings may represent the link between in vitro studies demonstrating atheroprotective effects of anti-PC IgM and clinical data demonstrating that low anti-PC IgM levels are associated with adverse outcome in CAD patients.